Structural Model of Motivation and Leadership Effects on Teacher Loyalty Mediated by Job Satisfaction in Indonesia - Juli Kurniawan; Tri Joko Rahardjo; Titi Prihatin (The Journal of Educational Development, 2025)
Teacher loyalty represents a strategic factor supporting institutional sustainability in private secondary education, where teacher turnover frequently challenges organizational stability. Previous studies have examined motivation and leadership influences on teacher retention; however, limited empirical evidence explains the mediating role of job satisfaction within an integrated structural relationship model. The present study analyzes the effects of work motivation and principal leadership on teacher loyalty mediated by job satisfaction in private junior secondary schools in Indonesia. A quantitative research design was applied using survey data collected from 102 teachers through structured questionnaires. Path analysis combined with Sobel mediation testing and classical assumption procedures was employed to evaluate direct and indirect relationships among variables. Results demonstrate that work motivation and principal leadership show limited direct influence on teacher loyalty, while job satisfaction significantly mediates the relationship between predictor variables and loyalty outcomes. Mediation analysis explains 79.9% of teacher loyalty variance through job satisfaction mechanisms. Findings contribute empirical evidence supporting job satisfaction as a central mechanism strengthening teacher loyalty and provide strategic implications for leadership practices and motivation-based management in private educational institutions.